Implementasi Program Ekstrakurikuler Tahfidz Di SMP Negeri 2 Kamang Magek (Tazakka: Jurnal Pendidikan dan Keislaman, 2024)
Tahfidz is an optional extracurricular activity that is not mandatory. Student interest in participating in the Tahfidz extracurricular program is very low; out of 127 students, only 9 are involved. The purpose of this study is to explore the program, implementation, and reasons behind the low interest of students in participating in the Tahfidz extracurricular activities at SMP Negeri 2 Kamang Magek. The method used is qualitative, with a case study approach. Data collection techniques include observation, interviews, and documentation. The data were analyzed through data reduction, data presentation, and drawing conclusions. The validity of the data was ensured through source and technique triangulation. The study reveals three key findings. First, the Tahfidz activity program is divided into two parts: short-term, which fulfills the extracurricular requirements at school, and long-term goals. Second, the implementation involves students being assigned to memorize at home, then reviewing and presenting their memorization to the supervising teacher at school. After completion, the teacher checks and initials the Tahfidz control book. Students who have completed their current memorization move on to the next verse, with a minimum requirement of memorizing 5 verses. Those who do not meet this requirement are not allowed to go home. Third, the low interest in participating in Tahfidz extracurricular activities is attributed to difficulties in memorization, lack of fluency in reading the Qur'an, lack of self-motivation, the simultaneous scheduling of Tahfidz with other extracurricular activities, insufficient encouragement from family, and peer influence.
Keywords: Interests; Extracurricular; Tahfidz